The Effect of Adding Natural Coloring from Mangosteen Peel (Garcinia mangostana L.) on the Organoleptic Characteristics of Putu Ayu Cake - Alvin Rosyid Auwaliansyah; Miftachul Chusnah (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
Mangosteen peel (Garcinia mangostana L.) is an agricultural waste product that has the potential to be used as a natural additive in food products because it contains natural pigments and various bioactive compounds. This study aims to determine the effect of adding mangosteen peel extract on the organoleptic characteristics of putu ayu cake, including color, texture, taste, and aroma, and to determine the treatment that produces the best organoleptic characteristics. The study used a quantitative experimental approach with a Completely Randomized Design (CRD) consisting of three treatments, namely P, Q, and R, with three replications. Organoleptic testing was conducted using the hedonic test method involving 15 untrained panelists. The research data were analyzed using Analysis of Variance (ANOVA) at a significance level of 5% and continued with the Least Significant Difference Test (LSD) of 5% if there were significant differences between treatments. The results showed that the addition of mangosteen peel extract had an effect on the level of panelists' preference for the organoleptic characteristics of putu ayu cake. Based on the determination of the best treatment in the draft, treatment R obtained the highest value in the color parameter of 11.93, texture of 12.00, taste of 12.47, and aroma of 13.00. Thus, treatment R was declared the best and most acceptable treatment by the panelists. This study shows that mangosteen peel extract has the potential to be used as a natural additive in the development of putu ayu cake products while increasing the added value of mangosteen peel waste.